2019
DOI: 10.1084/jem.20181049
|View full text |Cite
|
Sign up to set email alerts
|

Vasculature-associated fat macrophages readily adapt to inflammatory and metabolic challenges

Abstract: Tissue-resident macrophages are the most abundant immune cell population in healthy adipose tissue. Adipose tissue macrophages (ATMs) change during metabolic stress and are thought to contribute to metabolic syndrome. Here, we studied ATM subpopulations in steady state and in response to nutritional and infectious challenges. We found that tissue-resident macrophages from healthy epididymal white adipose tissue (eWAT) tightly associate with blood vessels, displaying very high endocytic capacity. We refer to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
181
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(187 citation statements)
references
References 72 publications
4
181
1
1
Order By: Relevance
“…While pseudo-time analysis of our scRNA-seq data indicated that Cd206 macrophage may represent a post-Cd11c stage of macrophage differentiation (Fig 5), the distinct distribution of the two macrophage populations in the cLP (Fig 6) and their unequal dependence on IRF5 (Fig 7) suggest that they may emerge independently in specific environmental niches. Indeed, two recent publications have described the predominance of two subpopulations of macrophages identified by scRNAseq in multiple tissues with distinct localisations 62,63 Throughout the MNP compartment of the inflamed intestine IRF5 broadly modulated biological pathways related to leukocyte activation, response to bacterium, pattern recognition receptor signalling pathway and regulation of T-cell activation (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…While pseudo-time analysis of our scRNA-seq data indicated that Cd206 macrophage may represent a post-Cd11c stage of macrophage differentiation (Fig 5), the distinct distribution of the two macrophage populations in the cLP (Fig 6) and their unequal dependence on IRF5 (Fig 7) suggest that they may emerge independently in specific environmental niches. Indeed, two recent publications have described the predominance of two subpopulations of macrophages identified by scRNAseq in multiple tissues with distinct localisations 62,63 Throughout the MNP compartment of the inflamed intestine IRF5 broadly modulated biological pathways related to leukocyte activation, response to bacterium, pattern recognition receptor signalling pathway and regulation of T-cell activation (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that macrophages are reprogrammed into an inflammatory phenotype in the setting of obese animals (Hotamisligil, 2017;Hume, 2015;Lumeng et al, 2007a;Lumeng et al, 2007b;McLaughlin et al, 2017;Nguyen et al, 2007;Odegaard et al, 2008;Pollard, 2009), although it is also suggested that they may protect mice against metabolic syndrome (Satoh et al, 2013;Wolf et al, 2017). Recognition of phenotypic and developmental heterogeneity (Coats et al, 2017;Gomez Perdiguero et al, 2015;Hassnain Waqas et al, 2017;Mass et al, 2016;Schulz et al, 2012;Silva et al, 2019;Zeyda et al, 2010) in adipose tissue macrophages lead to the hypothesis that distinct populations may mediate separate functions (Coats et al, 2017;Kratz et al, 2014;Silva et al, 2019;Zeyda et al, 2010). Here, we re-examined the roles of adipose macrophages in the context of their developmental origins, and identified an essential and evolutionarily conserved role of embryo-derived resident adipose tissue macrophages in establishment and control of lipid storage by specialized fat-storing tissues.…”
Section: Main Textmentioning
confidence: 99%
“…Mϕs are another important resident cell type in visceral adipose tissue. Activated Mϕs in obese adipose tissue are derived from multiple, distinct obese‐associated cell populations recently identified via transcriptome and functional analyses 38,39 . In obese adipose tissue, a distinct class of metabolically activated Mϕs contributes to metabolic dysfunction and insulin resistance 38,40,41 .…”
Section: The Systemic and Local Effects Of Adipose Eosinophils In Obementioning
confidence: 99%